Developing Micro Waqf Bank in Indonesia: A Delphi-SWOT Analysis - Fatin Fadilah Hasib; Aam Slamet Rusydiana (SMART Insight, 2022)
This study uses SWOT analysis which produces a SWOT matrix and several alternative strategic options (SO, ST, WO, and WT strategies). This study also uses the Delphi technique to select priority strategies for the development of Micro Waqf Banks (BWM) in Indonesia. Sources of data obtained from observations, interviews, and literature reviews. Interviews were conducted with practitioners, experts, regulators and academics. There are 6 alternative strategies for the development of BWM in Indonesia. The priority strategy of the 6 strategies is socialization and education about BWM to all groups.